ANALISIS PEMAHAMAN GURU DAN SISWA PADA KELAS RENDAH TERHADAP PEMBELAJARAN STEAM DI SD NEGERI SODONG 02 BATANG - Nisaul Mufida; Arfilia Wijayanti; Duwi Nuvitalia (STKIP Subang, 2022)
The purpose of this study was to find out how the understanding of teachers and low class students towards STEAM learning at SD Negeri Sodong 02 Batang. The data obtained were processed using qualitative descriptive techniques using data triangulation consisting of interviews, observations, and questionnaires. The understanding of teachers and low class students towards STEAM learning at SD Negeri Sodong 02 Batang has been carried out well, but has not been maximized in student questionnaire activities. The results of the observation that the average percentage of teachers' understanding of STEAM learning is 93.75% in the very good category, and students in the low class is 75% in the good category. Then, the results of the questionnaire, the average percentage of teachers' understanding of STEAM learning is 91.6% in the very good category, and students in the low class is 42.55% in the sufficient category. Based on data analysis and discussion that STEAM (Science, Technology, Engineering, Art, and Mathematics) learning is able to increase student activity in teaching and learning activities.